2020
DOI: 10.1021/acs.jpclett.0c03030
|View full text |Cite
|
Sign up to set email alerts
|

Single-Molecule Observations Provide Mechanistic Insights into Bimolecular Knoevenagel Amino Catalysis

Abstract: While single-molecule (SM) methods have provided new insights to various catalytic processes, bimolecular reactions have been particularly challenging to study. Here, the fluorogenic Knoevenagel condensation of an aromatic aldehyde with methyl cyanoacetate promoted by surface-immobilized piperazine is quantitatively characterized using super-resolution fluorescence imaging and stochastic analysis using hidden Markov modeling (HMM). Notably, the SM results suggest that the reaction follows the iminium intermedi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 52 publications
0
10
0
Order By: Relevance
“…Because the intensity of each frame in the trajectory was calculated by averaging the intensities of the 3 × 3 pixels (330 × 330 nm 2 ) area around the center position of the bright spot, the result indicated that repetitive nonspecific adsorptions could occur within the 3 × 3 pixels area. Thus, to minimize the influence of nonspecific adsorption on the analysis of single-molecule events, e.g., the fluorogenic reactions or the turnovers involving fluorescently labeled reactants, , it is better to make sure that the time intervals between target events are much shorter than the average interval τ i of nonspecific adsorptions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Because the intensity of each frame in the trajectory was calculated by averaging the intensities of the 3 × 3 pixels (330 × 330 nm 2 ) area around the center position of the bright spot, the result indicated that repetitive nonspecific adsorptions could occur within the 3 × 3 pixels area. Thus, to minimize the influence of nonspecific adsorption on the analysis of single-molecule events, e.g., the fluorogenic reactions or the turnovers involving fluorescently labeled reactants, , it is better to make sure that the time intervals between target events are much shorter than the average interval τ i of nonspecific adsorptions.…”
Section: Resultsmentioning
confidence: 99%
“…The applications of single-molecule fluorescence imaging have been growing fast in the past decades, particularly in biochemical research, including biochemical reactions, biomolecule interactions, and super-resolution imaging. Single-molecule imaging provided insights into the heterogeneity and dynamic properties of individual molecules that were usually hidden in bulk measurements due to the averaging effect. Because of the advantages, single-molecule imaging has also been used to study heterogeneous catalysis of nanomaterials. , Recently, there has been a growing interest in studying organic reactions by single-molecule fluorescence imaging. To achieve that, it is critical to keep the fluorescent molecules well separated in space with low fluorescence background. The surface preparation procedure has been well developed for single-molecule fluorescence imaging of biomolecules in aqueous solutions. However, little has been done to optimize the surface preparation procedure for single-molecule fluorescence imaging in organic solvents. , Compared to water, organic solvents typically contain higher percentage of impurities that are almost impossible to remove completely.…”
Section: Introductionmentioning
confidence: 99%
“…Another case study wherein single-molecule fluorescence microscopy techniques were used to distinguish between two plausible reaction mechanisms is the Knoevenagel condensation reaction, which is the condensation of an active methylene with an aldehyde in the presence of amine catalyst [34]. There are two plausible options for the mechanistic role of the amine: base catalyst Preparative synthetic chemistry: preparative chemistry, synthetic chemistry, or bench-scale chemistry is chemistry on the macroscale; chemistry on a sufficiently large scale for product isolation and use.…”
Section: Highlightsmentioning
confidence: 99%
“…In organic solvents [3,44] Under air-free conditions (glovebox setup and adding solid reagents during imaging) [4,5] Imaging in flow cells [9,32,52] Higher temperature imaging (diffusion at 135°C, chemical reaction at 45°C) [24,52] Types of reactions and processes imaged Hydrolysis [6] Proton-transfer [53] Epoxidation [26,33] Solubilization [4,36] Deallylation [5] Redox (nanoparticle and photocatalysis) [10,11,17,[19][20][21]54] Cross-coupling [46] Oligomerization [14] Polymerization [40][41][42]55] Hydrogenation [56] Cycloaddition [47][48][49][50] Condensation [34,57] Corrosion [15,16] Molecular metal-ligand exchange/dissociation [37][38][39]44] Oxidative addition [4,35,46] Mechanistic questions answered Identification of previously unknown organic and organometallic intermediates …”
Section: Reaction Conditionsmentioning
confidence: 99%
See 1 more Smart Citation